Preparing a Speech - James E. Dyer (EDIS)
WC086, a 6-page fact sheet by James E. Dyer, addresses preparing to deliver a speech through audience analysis, considering a purpose and topic, preparing the major components of the speech (introduction, main point, organization, and conclusion), and referencing resources. Includes useful resources. Published by the UF Department of Agricultural Education and Communication, December 2008.